(untitled) - Sedliak, Marian; Sulgan, Marian (Doprava a spoje, 2012)
This contribution presents the basic cost model which could help the manufacturing plants to identify the main factors affecting the different cost types when considering the suitability of establishing Just-in-Sequence supply.